Routing method based on multicriteria optimization and fuzzy logic - Буханько, Олександр Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
In work there is presented a routing method based on multicriteria optimization and fuzzy logic apparatus. The program complex was developed for proposed method investigation